Labour market policies, strategies and statistics for people with disabilities: A cross-national comparison - Anders Bergeskog (Institute for Labour Market Policy Evaluation (IFAU), 2001)
In addition to describing different countries labour market policies for people with disabilities, this study attempts to establish some initial benchmarks for comparing national policies in this respect for a number of OECD countries. The report systematically compares the countries in order to provide answers as to how they differ with respect to: (1) the target groups labour force participation and employment rate; (2) what labour market programmes are applied and to what degree; (3) to what extent the regular policy and institutional framework is used to integrate persons with disabilities into the labour market (the degree of mainstreaming). The study is based on a questionnaire to national government departments in all the OECD-countries in 1999. Of the 21 countries which are compared, Sweden, New Zealand, Germany and France have high labour market participation rates, while Spain, Ireland, Poland, Greece and Italy are all below average. Eleven countries provided sufficient information for a thorough cross-national comparison which among other things includes detailed descriptions of each countrys labour market programmes and statistics on the number of participants with disabilities and disability pension recipients. Despite similar labour force participation figures in Great Britain, Australia, Finland, Norway and Austria, the latter two countries have a substantially higher proportion of people in labour market programmes. Likewise, labour force participation in New Zealand is about the same as in Sweden, despite fewer participants in programmes. The proportion of participants with disabilities in various types of programmes specially targeted for people with disabilities and general programmes are compared. In Sweden, almost half the participants with disabilities in labour market programmes are employees with long-term wage subsidies. Almost half the participants in labour market programmes in Finland and Norway are undergoing training. Labour market training is also important in English-speaking countries and so are work experience programmes and, in principle, there are no long-term wage subsidies. Both the proportion of disability pension recipients and the proportion of programme participants are limited in Australia and the United Kingdom, while both proportions are substantial in Sweden and Ireland.
Keywords: J15; J18; J21; 330; Labour market policy; People with disabilities; Mainstreaming; Labour force participation; Labour market programmes; Disability pension; Benchmarking; Cross-national comparison; OECD countries